1996
DOI: 10.1007/s001170050067
|View full text |Cite
|
Sign up to set email alerts
|

Erste Ergebnisse der MRT-gesteuerten laserinduzierten interstitiellen Thermotherapie von Kopf- und Halstumoren

Abstract: Laser-induced interstitial thermo-therapy (LITT) was introduced as a minimally invasive form of therapy for tumors in different anatomic regions. However, in the orofacial region, it has not been used so far for inoperable T4 carcinomas. Since vascular and neural structures are often close to the tumor or are even involved, online monitoring of LITT is necessary. The aim of our study was to establish a method of monitoring LITT with MRI (magnetic resonance imaging) in the orofacial region. Five patients with T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…The Signa SP open MRI allows operations to be performed under continuous imaging (almost real‐time imaging). Despite the rather small gap (58 cm) between the magnetic coils, the device offers many possibilities for performing minor operations and biopsies in the head and neck region 2, 3. Access for operative procedures is better than in horizontally open MRIs, in which only minor biopsies can be performed under constant imaging 4.…”
Section: Discussionmentioning
confidence: 99%
“…The Signa SP open MRI allows operations to be performed under continuous imaging (almost real‐time imaging). Despite the rather small gap (58 cm) between the magnetic coils, the device offers many possibilities for performing minor operations and biopsies in the head and neck region 2, 3. Access for operative procedures is better than in horizontally open MRIs, in which only minor biopsies can be performed under constant imaging 4.…”
Section: Discussionmentioning
confidence: 99%
“…Using an animal tumor model to investigate local recurrence, Maker et al (1995) observed that Nd:YAG contact laser ablation provided about 50% improvement in the control of local disease in vivo (p< 0.05) compared to animals treated with a scalpel. Pilot studies have demonstrated that Nd:YAG (1064 nm) laser induced thermal therapy may also play a role in pain control and allow continued nutritional support for patients with advanced or recurrent head and neck tumors (Castro et al, 1995a;Castro et al, 1994;Jager et al, 1996) Through repeated laser endoscopy, the need for a nasogastric or gastrostomy tube has been avoided as well Mitty et al, 1996). Several studies report successful relief of malignant dysphagia and improvement in the quality of life with endoscopic Nd:YAG laser treatment (Karlin et al, 1987;Mitty et al, 1996;Sawant and Moghissi, 1994).…”
Section: Clinical Relevance Of Laser and Cisplatin In Photo Chemotherapymentioning
confidence: 99%
“…Lasers employ the principle of stimulated photon emission to produce light that markedly differs in quality, depending on the wavelength of the radiation in ultraviolet (UV), infrared (IR) or visible regions of the spectrum (Joffee et al, 1989). In this context, laser fiber optics have been used for minimally invasive access and treatment of inoperable cerebral and head and neck neoplasms as well as tumors in other organs and systems Jager et al, 1996;Vogl et al, 2002a;Vogl et al, 2002b). For the past 50 years, several laser technologies have been employed in surgical oncology, including CO 2 laser for cutting and coagulating and laser-induced thermal therapy (LITT) for thermal ablation of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Die Intensitätsabnahme des Signals in den T2-gewichteten Sequenzen blieb in einem gewissen Maû auch nach Rückgang der Temperatur auf das Ausgangsniveau bestehen. Sie muû daher im Gegensatz zu ausschlieûlich temporären Signalintensitätsabnahmen in T1-gewichteten Sequenzen, die während der interstitiellen Koagulation bei verschiedenen Organen wie Leber [24,28], Tumoren im Hals-Nasen-Ohren-Bereich [3,16,27] und Prostata [20] gemessen wurden, nicht nur die Zunahme der Temperatur, sondern auch die Ausdehnung der Koagulation repräsentieren. Dafür spricht auch, daû der Abfall der Intensität pro C in der Erwärmungsphase wesentlich stärker ausgeprägt war, als der Wiederanstieg der Intensität in der Abküh-lungsphase.…”
Section: Diskussionunclassified